Prabowo Subianto's Political Branding on Instagram in the 2024 Presidential Election - Pratama, Galih; Irwanti, Marlinda; Mowafg Masuwd (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
New media, especially Instagram, has emerged as a new chapter in the discourse of utilizing political marketing of an actor, such as the @prabowo.gibran2 account. This research aims to discover Prabowo's political branding on Instagram and its relevance to George Herber Mead's symbolic interactionism theory. This research uses an interpretive social paradigm, and the research methodology uses virtual ethnography by accessing, researching, and analyzing media spaces, media documents, media objects, and user experiences. The research results show that Prabowo's political branding includes a free lunch and milk program as a policy, joget gemoy as a candidate person, and a new direction of downstream politics as a party, providing ideology, structure, and vision-mission. As for George Herber Mead's view of self, joget gemoy is a reflex action of the organism and a realization and presentation of self in social situations. Second, related to the view of mind, the encounter between thoughts and symbols related to two fingers in the form of a Korean hand heart and the definition of the situation: Gibran's appointment as vice president is a foresighted choice of segmentation and downstream. Third, related to the view of society, two discoveries about the proof of universal democracy, namely, the white shirt as a sign of Jokowi-Prabowo reconciliation and the reconciliation of political figures.